Demand for parking and its contribution to the search parking strategies: Case of UiTM Pahang / Nor Aziah Abd Kadir and Khalid Mat Pardi - Abd Kadir, Nor Aziah; Mat Pardi, Khalid (2013)
The frustrations among drivers who are unable to find a parking space were common among the staff in UiTM Pahang especially when the demanded parking spaces were fully occupied. It may cause the drivers to circle the streets in order to find an empty parking spot and mostly will end up by parking illegally along the street. This situation creates havoc to the public where it may interrupt the traffic flow and increase the risk of accidents. Thus, this paper was to examine the factors that contribute to the parking search strategies used by the drivers to get to their intended destination. The observation and interview were done in order to get the information. As a result, we have concluded that the drivers used six strategies in searching for parking in the campus. The choices of strategies were based on the reasoned behaviour and automatic behaviour.